Critically Mediterranean Temporalities, Aesthetics, and Deployments of a Sea in Crisis (Mediterranean Perspectives, 2018)
Traversed by masses of migrants and wracked by environmental and economic change, the Mediterranean has come to connote crisis. In this context, Critically Mediterranean asks how the theories and methodologies of Mediterranean studies may be brought to bear upon the modern and contemporary periods. Contributors explore how the Mediterranean informs philosophy, phenomenology, the poetics of time and space, and literary theory. Ranging from some of the earliest twentieth-century material on the Mediterranean to Edmond Amran El Maleh, Christoforos Savva, Orhan Pamuk, and Etel Adnan, the essays ask how modern and contemporary Mediterraneans may be deployed in political, cultural, artistic, and literary practice. The critical Mediterranean that emerges is plural and performative-a medium through which subjects may negotiate imagined relations with the world around them. Vibrant and deeply interdisciplinary, Critically Mediterranean offers timely interventions for a sea in crisis.